Factors contributing to the development of an HIV ministry within an African American church. - Stewart, Jennifer M; Dancy, Barbara L (The Journal of the Association of Nurses in AIDS Care : JANAC, 2012)
Having an HIV ministry within a church depends on the religious culture of that church. However, little is known about how a church's religious culture influences an HIV ministry. This study's purpose was to examine how an African American church's religious culture supported the development, implementation, and maintenance of an HIV ministry within the church. An ethnographic case study research design was used. Data were collected through interviews, nonparticipant and participant observations, review of pertinent documents, and survey of congregants. Results revealed the following as important for an HIV ministry: (a) a belief in helping others and treating everyone with respect and dignity, (b) feelings of compassion toward individuals infected with HIV, and (c) HIV education. This information can assist in developing interventions to enhance the African American church movement toward HIV ministries.
Keywords: African Continental Ancestry Group; HIV Infections; Humans; Religion